Assessment of cross-laminated timber panels by the state-space approach. Issue 11 (August 2019) - Albostami, Asad S; Wu, Zhangjian; Cunningham, Lee S
In this article, cross-laminated timber panels are investigated as a novel engineering application of the state-space approach. As cross-laminated timber is a laminated composite panel, the three-dimensional analytical method provided by the state-space approach offers the potential for improved accuracy over existing common approaches to the analysis of cross-laminated timber. Before focusing on the specific application to cross-laminated timber, the general theory of the state-space approach is outlined. The method is then applied to describe the behaviour of a number of cross-laminated timber panel configurations previously examined experimentally and analytically. In order to demonstrate the capability of the state-space approach in this application, the results are compared with those from various two-dimensional and three-dimensional analytical approaches and finite element modelling briefly. With a view to design, different failure criteria are explored to assess the ultimate strength of the cross-laminated timber panels. The state-space approach demonstrates its superior capability in capturing the nonlinear distribution of the elastic stresses through the thickness of the cross-laminated timber panels over a range of span-to-thickness ratios common in practical applications.